Synthesis of mesogenic phthalocyanine-C60 donor–acceptor dyads designed for molecular heterojunction photovoltaic devices - Geerts, Yves Henri; Debever, Olivier; Amato, Claire; Sergeyev, Sergey (Beilstein Journal of Organic Chemistry, 2009)
A series of phthalocyanine-C60 dyads 2a–d was synthesized. Key steps in their synthesis are preparation of the low symmetry phthalocyanine intermediate by the statistical condensation of two phthalonitriles, and the final esterification of the fullerene derivative bearing a free COOH group. Structural characterization of the molecules in solution was performed by NMR spectroscopy, UV–vis spectroscopy and cyclic voltammetry. Preliminary studies suggest formation of liquid crystalline (LC) mesophases for some of the prepared dyads. To the best of our knowledge, this is the first example of LC phthalocyanine-C60 dyads.
Keywords: donor–acceptor dyad; fullerene; liquid crystals; phthalocyanine; phthalonitrile